AB0252 Loosing das28-esr, but staying in boolean remission- is it possible? data from the prospective, randomised retro trial on rheumatoid arthritis patients in stable remission. (12th June 2018) - Erhard, J.; Hagen, M.; Englbrecht, M.; Haschka, J.; Reiser, M.; Kleyer, A.; Hueber, A.J.; Manger, B.; Figueiredo, C.; Cobra, J.F.; Tony, H.-P.; Finzel, S.; et al.
Abstract : Background: DAS28-ESR is the most widely used instrument to assess remission in rheumatoid arthritis (RA) patients. Nonetheless, substantial residual disease activity can be present in RA patients fullfilling DAS28-ESR remission. Therefore, more stringent criteria for remission have been developed. While it is known that patients can fulfil DAS28-ESR but fail ACR/EULAR Boolean remission criteria, the existence of the reverse is less known. Objectives: To test the possibility to loose DAS28-ESR remission while staying in ACR/EULAR remission in patients with RA Methods: Data were obtained from the prospective randomised RETRO study (EudraCT: 2009–015740–42), which recruits RA patients in stable remission. Remission was assessed by the following instruments every three months: DAS28-ESR, DAS28-CRP, CDAI, SDAI, PAS, and ACR/EULAR criteria. In the group of patients, escaping DAS28-ESR remission, but fulfilling ACR/EULAR Boolean remission, the individual components of DAS28-ESR were analysed that determined their escape from remission. Results: 142 patients analysed, which were all in DAS28-ESR remission at baseline. Of them, 140 (98.59%) were in DAS-CRP-remission, 131 (92.25%) in CDAI-remission, 130 (91.55%) in SDAI-remission, 109 (76.76%) in ACR/EULAR remission and 66 (46.48%) in PAS-remission. We analysed upon the 1 year follow up those patients loosing DAS28-ESR remission over time: 58 patients lost DAS-ESR remission at least once during the 4 follow-up visits. Surprisingly, 24% (3 months), 36% (6 months), 24% (9 months) and 28% (12 months) of the patients still fulfilled the Boolean remission criteria. The only plausible reason for failing DAS28-ESR remission but staying in ACR/EULAR remission is an isolated elevation of the ESR, not accompanied by increased signs and symptoms of disease. Indeed all patients loosing DAS28-ESR remission but staying in ACR/EULAR Boolean remission had an elevated ESR equal or higher than 15 mm. However, if DAS28 scores were calculated by C-reactive protein in the same patients, they all fulfilled remission criteria. Conclusions: DAS28-ESR remission can be missed even if a patient fulfils the more stringent ACR/EULAR Boolean remission criteria. The reason for this remarkable constellation is an elevated erythrocyte sedimentation rate without any clinical symptoms. Hence, isolated elevations of erythrocyte sedimentation rate should be seen critical. These data show the limitations of individual instruments to assess remission in RA and show that interpretations of the erythrocyte sedimentation rate need to be done in the clinical context Disclosure of Interest: None declared